ORGANIZATION OF COMPETITIVE DUEL GAMES - Živanović, Milan V (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
Play is the basic child activity in preschool period. Its attractiveness for the children of that age has been used for educational purposes by including cognitive content and goals into play activities. In middle, and, particularly, in senior and preparatory preschool group there is more interest for games of competitive nature. In this respect, the role of teacher is not merely limited to good knowledge and selection of competitive games; it also concerns their organization depending on special, time-wise, technical and population-wise conditions. In our pedagogical literature very little has been written on this topic. Hence, it no surprise that this issue is omitted in curricula of preschool teacher training colleges. The goal of this text is to emphasize the importance of proper organization of competitive duel games and describe the most common types of those competitions in practice.
Keywords: game; preschool education; organization competitiveness; Round-robin tournament; elimination tournament